Truth in Practical Reason: Practical and Assertoric Truth in Aristotle’s Nicomachean Ethics - Pantoulias, Michail; Vergouli, Vasiliki; Thanassas, Panagiotis (Peitho. Examina Antiqua, 2021)
Truth has always been a controversial subject in Aristotelian scholarship. In most cases, including some well-known passages in the Categories, De Interpretatione and Metaphysics, Aristotle uses the predicate ‘true’ for assertions, although exceptions are many and impossible to ignore. One of the most complicated cases is the concept of practical truth in the sixth book of Nicomachean Ethics: its entanglement with action and desire raises doubts about the possibility of its inclusion to the propositional model of truth. Nevertheless, in one of the most extensive studies on the subject, C. Olfert has tried to show that this is not only possible but also necessary. In this paper, we explain why trying to fit practical truth into the propositional model comes with insurmountable problems. In order to overcome these problems, we focus on multiple aspects of practical syllogism and correlate them with Aristotle’s account of desire, happiness and the good. Identifying the role of such concepts in the specific steps of practical reasoning, we reach the conclusion that practical truth is best explained as the culmination of a well-executed practical syllogism taken as a whole, which ultimately explains why this type of syllogism demands a different approach and a different kind of truth than the theoretical one.